The Eskimo : the Inuit and Yupik people - Osinski, Alice (Chicago : Childrens Press, 1985)
Describes the natural environment and traditional way of life of the Eskimos, contrasting their old customs with the new lifestyle brought by modern civilization.
Includes index.
School Library Journal
Booklist
4.2
K-3
Keywords: Yupik Eskimos -- Juvenile literature; Eskimos; Inuit